A case of familial hemiplegic migraine associated with a novel ATP1A2 gene mutation. - De Cunto, Angela; Bensa, Marco; Tonelli, Alessandra (Pediatr Neurol, 2012)
Hemiplegic migraine constitutes an unusual form, characterized by periodic attacks of migraine with a motor component (hemiplegia). Familial forms are dominantly inherited, and are attributable to mutations in genes encoding proteins involved in ion transportation, including ATP1A2, which codes for the α-2 isoform of the sodium-potassium adenosine triphosphatase, a P-type cation transport adenosine triphosphatase, and responsible for the so-called familial hemiplegic migraine type 2. We describe a 9-year-old boy affected by familial hemiplegic migraine, with a novel ATP1A2 gene mutation (c.1799T>C p.V600A) in exon 13. Long-term treatment with flunarizine resulted in a good clinical response and the prevention of further attacks.
Keywords: Amino Acid Sequence; Child, Preschool; Humans; Male; Migraine with Aura; Molecular Sequence Data; Mutation; Pedigree; Sodium-Potassium-Exchanging ATPase